Prediksi Kinerja Karyawan Berlandaskan Disiplin Kerja dan Lingkungan Kerja Era Kenormalan Baru - Hartono, Ludy; Milfayetty, Sri; Foo, Mariana (Universitas Muhammadiyah Surakarta, 2023)
Abstract. This study aims to test relationship between work discipline and work environment with employee performance at PT Makmur Dekorindo Lestari Medan. The population in this study were 99 employees and all of them became the total sample in this study as many as 99 respondents. The employee performance scale represents assessments on task performance, work behavior, and counter-productive behavior. The work discipline scale represents assessments on time observance, job responsibility, and understanding regulations. The work environment scale represents assessments on physical work environment and non-physical work environment. The research method used was quantitative research with correlational approach using multiple linear regression equations. The hypothesis put forward that good work discipline and work environment can predict the possibility of a significant relationship in the realization of good employee performance simultaneously considered acceptable by proving the calculated Fcount of 66,653 Ftable of 3,091. The invention in this study reveals that work discipline and work environment have a strong relationship (r=0,762) with employee performance simultaneously. Employee performance is only half of the probability (57,2%) predicted by work discipline and work environment. Employees who can display good work discipline and can perceive good work environment have implication for better employee performance. Other interesting invention in this study amidst development of intergenerational issues reveals that the older the employee, the more contribution of work discipline and work environment in predicting employee performance.Keywords: Employee performance; work discipline; work environment